2021
DOI: 10.1111/1744-9987.13636
|View full text |Cite|
|
Sign up to set email alerts
|

Median nerve swelling is an independent risk factor of carpal tunnel syndrome in chronic hemodialysis patients

Abstract: Carpal tunnel syndrome (CTS) has a wide variety of underlying causes and occurs in association with dialysis. Early diagnosis is essential to prevent permanent nerve damage and functional sequelae. We evaluated the association between CTS and cross-sectional area (CSA) of the median nerve in chronic hemodialysis (HD) patients. Patients with end-stage renal disease on maintenance HD via arteriovenous fistula were enrolled. We divided 43 patients into two groups; patients diagnosed with CTS (n = 19) and patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…In addition, there are many other hypotheses about the etiology of tendinopathy in ESKD and dialysis patients. For example, some studies suggested that β2-microglobulin introduced amyloidosis in the tendon of dialysis patients may be the cause of tendon thickening and other symptoms of nerve damage [31][32][33]. Our results revealed that the tendon thickness in ESKD patients tends to be higher than in normal people; however, the observed difference was not statistically different, which may be partly due to the insufficient number of cases in our groups, and partly due to the possible differences in the degree of systemic tendon amyloidosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are many other hypotheses about the etiology of tendinopathy in ESKD and dialysis patients. For example, some studies suggested that β2-microglobulin introduced amyloidosis in the tendon of dialysis patients may be the cause of tendon thickening and other symptoms of nerve damage [31][32][33]. Our results revealed that the tendon thickness in ESKD patients tends to be higher than in normal people; however, the observed difference was not statistically different, which may be partly due to the insufficient number of cases in our groups, and partly due to the possible differences in the degree of systemic tendon amyloidosis.…”
Section: Discussionmentioning
confidence: 99%
“…This review included a total of 42 articles investigating the association between diabetes and the occurrence of carpal tunnel syndrome, with a combined study population of 3,377,816 participants between 1991 and 2022 [3,5,17,19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Geographically, 15 studies with 1,332,085 participants were conducted in America, 12 studies with 19,792 participants were carried out in Europe, and 15 studies with 1,019,692 participants were conducted in Asia.…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
“…Numerous studies have been conducted worldwide in recent years to investigate the relationship between diabetes and CTS, with a significant proportion of them demonstrating that diabetes increases the risk of developing CTS [3,5,[21][22][23][24][25][26]. However, there are also studies that suggest that there is no association between diabetes and the occurrence of CTS [17,[27][28][29][30][31][32][33][34]. For instance, Wiberg et al (2022) investigated the association between diabetes and CTS in a UK population-based cohort of over 400,000 people.…”
Section: Introductionmentioning
confidence: 99%